Young man Luther : a study in psychoanalysis and history - Erikson, Erik H. (Erik Homburger), 1902-1994 (New York : The Norton Library, W.W. Norton& company. INC., 1958)
"In this psychobiography, Erik H. Erikson brings his insights on human development and the identity crisis to bear on the prominent figure of the Protestant Reformation, Martin Luther."--Publisher's description.
Case and event -- The fit in the choir -- Obedience -- to whom? -- Allness or nothingness -- First mass and dead ends -- The meaning of "meaning it" -- Faith and wrath -- Epilogue.
Originally published: 1958
Includes bibliographical references (pages 269-277) and index
Keywords: Luther, Martin, -- 1483-1546; Reformation -- Germany -- Biography; Germany -- Church history -- 16th century; Biographies